Japan's Future Embracing Multi-ethnic Complexities through Physical Education & the Martial Arts - Joan Neide (Universidad de León, 2012)
Japan is preparing for a major social change that is setting the stage for the revamping of the educational curriculum. The nation of Japan is planning for the first time to allow mass immigration in order to cope with a declining population. Public and private schools are gearing up for this major societal change and are seeking ways to internationalize the educational curriculum so that the next generation of Japanese will be able to easily assimilate into this new world. On Okinawa, an unlikely school subject, physical education, is being used to foster a global perspective and to develop what can be defined as an international character. The educational community is introducing Okinawan karate as a physical education requirement for graduation. Educators hope that the character traits that are developed through martial art training will aid in the acceptance and assimilation of the predicted new immigrants as the indigenous Japanese population declines.